Sunday School Teachers’ Stewardship for Children’s Faith Growth in The Community of Shalom at XYZ Church in Tangerang - Nostalgia Pax Nikijuluw (EDULEAD: Journal of Christian Education and Leadership, 2022)
Peran guru-guru sekolah minggu sangat berdampak bagi pertumbuhan iman anak sekolah minggu (ASM). Penelitian ini dilakukan untuk mengetahui makna penatalayanan para GSM bagi pertumbuhan iman di Gereja XYZ Tangerang. Pendekatan kualitatif dengan metode fenomenologi digunakan untuk menggali makna pengalaman pelayanan para GSM, khususnya GSM yang mengajar kelas anak usia dini di Gereja XYZ Tangerang. Hasil penelitian menunjukkan bahwa bagi para GSM yang mengajar kelas anak usia dini di Gereja XYZ Tangerang, pelayanan sebagai GSM adalah sebuah perjalanan dalam anugerah Tuhan, yang disikapi bersama dengan respons syukur dan ketaatan. Sikap yang membawa pada kesetiaan dalam melayani Tuhan, sebagai respons dari rasa syukur dan persembahan kepada Tuhan atas karunia keselamatan.AbstractSunday school teachers are church activists whose their presence impact the children’s faith growth. This study was conducted to determine the meaning of SST’ stewardship for faith growth in the XYZ Church Tangerang. A qualitative approach with the phenomenological method is used to explore the meaning of the service experience of the Sunday School Teacher' (SST), especially SST who teaches early childhood classes at the XYZ Church Tangerang. The result shows that the SST’s stewardship at early childhood classes in XYZ Church Tangerang  is a journey in God's grace, which is taken together with a response of gratitude and obedience. An attitude that leads to faithfulness in serving God, as a response to gratitude and offering to God for the gift of salvation.